A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages sentatives of the voluntary hospitals and they trust that it will be possible — without infringing the principles on which they believe the National Health Service should be founded — to avoid injury to the voluntary movement, and to ensure the cordial collaboration of the voluntary hospitals in the new service. Mental Hospitals The inclusion of the mental hospitals in the National Health Service presents some difficulty until a full restatement of the law of lunacy and mental deficiency can be undertaken. Yet, despite the difficulties, the mental health services should be taken over by the new joint authority. This will be in accord with the principle, declared by the Royal Commission on Mental Disorder, that the treatment of mental disorder should approximate as nearly to the treatment of physical ailments as is consistent with the special safeguards which are indispensable when the liberty of the subject is infringed. Hospitals for infectious disease In the counties isolation hospitals for infectious diseases are with few exceptions owned and administered by the minor authorities and not by the county councils, and their transfer to the new joint authority will mean that their present owners will give up ownership without retaining even the part interest which membership of the new joint authority will afford in the case of hospitals belonging to county and county borough councils. The case for this absolute transfer of the isolation hospitals has nothing to do with the past record of the minor authorities, nor is it in any way a reflection upon the quality of the work which they have hitherto done. The whole trend of medical opinion has for some time been in favour of treating these hospitals, not primarily as places for the reception of patients to prevent the spread of infection, but as hospitals where severe and complicated cases of infectious disease can receive expert treatment and nursing. The small isolation hospital of the past century is not only uneconomic in days of rapid transport but cannot reasonably be expected to keep abreast of modem methods. One result of the new outlook will be the development, in addition to the larger isolation hospital serving the densely populated area, of accommodation for infectious diseases in blocks forming part of the general hospitals. These considerations all indicate that the infectious disease hospitals must in future form part of the general hospital system. Inspection of Hospitals Apart from special inspections to enquire into difficulties that have arisen or changes that are in contemplation, routine inspections at not too frequent intervals will serve the double purpose of bringing to notice defects of organisation or management and, what is equally important, of enabling individual hospitals to be kept in touch with the latest practice and ideas. The foundation of any inspectorate must clearly be a team of highly qualified medical men, but the inspectors 15 36/H24/41